Sonata forms - Rosen, Charles (New York Norton & Company, 1988)
"Nobody writes better about music .... again and again, unerring insight into just the features that make the music special and fine."The New York Review of BooksCharles Rosen says of sonata form: "[It] is not a definite form like a minuet, a da capo aria, or a French overture; it is, like the fugue, a way of writing, a feeling for proportion, direction, and texture rather than a pattern."